BLUE RIVER CLEAN ACTION AND ENVIRONMENTAL CARE EDUCATION AS AN EFFORT TO DEVELOP SUSTAINABLE TOURISM IN BANABUNGI VILLAGE, PASARWAJO DISTRICT - Kabiruddin; Irunsah, Aslan; Suhartin; Ruzanna, Arina; Fitrianti (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Kali Biru, located in Banabungi Village, Pasarwajo District, Buton Regency, is one of the popular tourist destinations for domestic tourists, offering natural beauty that remains original and beautiful, as well as high accessibility. Although awareness of the importance of maintaining river cleanliness has increased, suboptimal waste management practices remain a significant challenge. This is due to the lack of intensive education on the importance of maintaining environmental cleanliness, especially rivers, as a tourism asset that has great potential in encouraging the economic growth of local communities. Clean-up and education actions about the importance of environmental cleanliness in the Kali Biru area were carried out using direct education methods, distribution of cleaning tools, and environmental cleaning in order to increase public and tourist awareness of the cleanliness of the river environment. The results of the evaluation show that the implementation of education and community empowerment programs in the Kali Biru tourist area is effective in increasing public understanding and affection for the importance of maintaining the cleanliness and preservation of the river environment as a tourist destination. This is expected to encourage sustainable economic growth through the development of responsible tourism.